High frequency of fraud in honey without sanitary inspection illegally sold in São Paulo State - FLORENTINO, Ana Paula; LIMA, Caroline da Veiga; MORANDINI, Giovana Galvão; SILVA, Guilherme Cardoso da; MORELLI, Laura Meiken; BATTISTIN, Lorena; PIVATO, Maria Eduarda Borges; SILVA, Max Sândalo Ferreira da; VIEIRA, Mayara Ferreira; CANUTE, Mayara de Sousa; PAULINO, Miguel Sionti de Medeiros; ARAUJO, Pedro Caldeira de; et al. (Food Science and Technology, 2023)
The aim of this study was to analyze honey from São Paulo State according to its physical and chemical properties. Determination of free acidity, moisture, hydroxymethylfurfural, Lund test, diastase test, and Fiehe reaction were performed in 73 samples (32 illegal honey, without sanitary inspection, and 41 legal honey, with sanitary inspection). An ANOVA test was applied to evaluate differences in the samples. Three samples had humidity greater than 20%, and one sample had a positive profile in the qualitative analysis of HMF (Fiehe) and quantitative analysis above 60 mg/kg. A total of 21 (65%) illegal honeys had at least one parameter outside the legislation. The irregularities presented were in the acidity, followed by the increase of HMF, negative Lund, high acidity, and high moisture. Significant differences were observed when comparing illegal and legal honey for acidity and hydroxymethylfurfural analysis (p < 0.05). The Fiehe test was positive in 2.44% of legal honeys and 64.52% of illegal honeys. No legal honey was negative for the Lund test, and 22.58% of illegal honeys had a negative profile. The results showed that illegal honey is not suitable for consumption, being outside the standard of identity and quality determined by the Codex Alimentarius Commission and the legislation.